Alpha Heating and Burning Plasmas in Inertial Confinement Fusion. (May 2016) - Betti, R.; Christopherson, A.R.; Bose, A.; Woo, K.M.
Abstract: Assessing the degree to which fusion alpha particles contribute to the fusion yield is essential to understanding the onset of the thermal runaway process of thermonuclear ignition. It is shown that in inertial confinement fusion, the yield enhancement due to alpha particle heating (before ignition occurs) depends on the generalized Lawson parameter that can be inferred from experimental observables. A universal curve valid for arbitrary laser-fusion targets shows the yield amplification due to alpha heating for a given value of the Lawson parameter. The same theory is used to determine the onset of the burning plasma regime when the alpha heating exceeds the compression work. This result can be used to assess the performance of current ignition experiments at the National Ignition Facility.